The influence of bio-based monomers on the structure and thermal properties of polyurethanes - Joanna Brzoska; Janusz Datta; Rafał Konefał; Václav Pokorný; Hynek Beneš (Scientific Reports)
Abstract Most polyurethanes (PU) are currently produced through the polyaddition reaction of polyisocyanates with polyols and chain extenders, using components of petrochemical origin. From an environmental and geopolitical point of view, and with regard to the problems of oil supply and processing, the replacement of petrochemical PU raw materials with renewable resources is highly desirable. It is also one of the principles of sustainable development and an important challenge for chemical companies and market competitiveness. Current research studies focus mainly on the use of bio-based polyols for PUs, while other PU components, in particular polyisocyanates, remain of petrochemical origin. In this work, a series of PUs have been synthesized by polyaddition reactions of different types of renewable polyols and bio-based polyisocyanates. The effects of the bio-derived components on the structure, thermal stability and phase transformations of the PU were studied using FTIR and NMR spectroscopy, SWAXS, TGA, DSC, DMTA and TGA-FTIR. A full conversion of the bio-based monomers was achieved in all cases, indicating good compatibility and reactivity of all bio-based components. It was observed that bio-based PU exhibited a lower degree of phase separation and slightly lower thermal stability compared to PUs from petrochemical monomers.